Max's story - Hawkins, Sarah (London : Red Fox, 2010)
Olivia's new retriever puppy from the Battersea Dogs & Cats Home, Max, is very clumsy and Olivia's parents soon lose patience with the puppy's messes, but Max knows just where to look when a magpie flies off with her mother's wedding ring. Includes information about the real Battersea Dogs & Cats Home and pet-themed puzzles.
4.4
3-6
3-6
Keywords: Battersea Dogs & Cats Home -- Juvenile fiction; Battersea Dogs & Cats Home -- Fiction; Battersea Dogs & Cats Home -- Fiction; Animal rescue -- Juvenile fiction; Girls -- Juvenile fiction; Puppies -- Juvenile fiction; Animal rescue -- Fiction; Animal shelters -- Fiction; Dogs -- Fiction; Girls -- Fiction; Animal shelters -- Fiction; Dogs -- Fiction; Girls -- Fiction